Comparing policy advisory systems beyond the OECD: models, dynamics and the second-generation research agenda. (4th July 2019) - Howlett, Michael
ABSTRACT: The concept of "policy advisory systems" was introduced by Halligan in 1995 as a way to characterize and analyze the multiple sources of policy advice utilized by governments in policy-making processes. The concept has proved useful and has influenced thinking about both the nature of policy work in different advisory venues as well as how these systems change over time. However, to date this work has examined mainly cases of developed countries and its application to developing and transitional countries is less certain. This paper sets out existing models of policy advisory systems based on Halligan's original thinking on the subject and assesses the findings of many existing studies into OECD countries that advisory systems have been changing as a result of the dual effects of increased use of external consultants and others sources of advice – "externalization" – and the increased use of partisan advice inside government itself – "politicization". Determining whether or not such changes have also characterized the situations found in developing and transitional countries and at the international-domestic and state-sub-state levels is the subject of the papers in this Special Issue.